Chemoselective and Site‐Selective Lysine‐Directed Lysine Modification Enables Single‐Site Labeling of Native Proteins. Issue 26 (20th April 2020) - Adusumalli, Srinivasa Rao; Rawale, Dattatraya Gautam; Thakur, Kalyani; Purushottam, Landa; Reddy, Neelesh C.; Kalra, Neetu; Shukla, Sanjeev; Rai, Vishal
Abstract: The necessity for precision labeling of proteins emerged during the efforts to understand and regulate their structure and function. It demands selective attachment of tags such as affinity probes, fluorophores, and potent cytotoxins. Here, we report a method that enables single‐site labeling of a high‐frequency Lys residue in the native proteins. At first, the enabling reagent forms stabilized imines with multiple solvent‐accessible Lys residues chemoselectively. These linchpins create the opportunity to regulate the position of a second Lys‐selective electrophile connected by a spacer. Consequently, it enables the irreversible single‐site labeling of a Lys residue independent of its place in the reactivity order. The user‐friendly protocol involves a series of steps to deconvolute and address chemoselectivity, site‐selectivity, and modularity. Also, it delivers ordered immobilization and analytically pure probe‐tagged proteins. Besides, the methodology provides access to antibody‐drug conjugate (ADC), which exhibits highly selective anti‐proliferative activity towards HER‐2 expressing SKBR‐3 breast cancer cells. Abstract : A chemical methodology finally addresses the undefeated challenge of modular and precision engineering of a Lys residue in a native protein. The remarkable control over selectivity provides the first‐ever approach to target Lys beyond the protein‐defined reactivity hotspot. This technology unfolds new gateways and renders analytically pure protein bioconjugates and homogeneous antibody‐drug conjugates.